Review of Animal Models to Study Pulp Inflammation - Davy Aubeux; Davy Aubeux; Davy Aubeux; Emmanuelle Renard; Emmanuelle Renard; Emmanuelle Renard; Fabienne Pérez; Fabienne Pérez; Fabienne Pérez; Solène Tessier; Solène Tessier; Valérie Geoffroy; et al. (Frontiers Media S.A., 2021)
Human dental pulp is a highly dynamic tissue equipped with a network of resident immunocompetent cells that play a major role in the defense against pathogens and during tissue injury. Animal studies are mandatory and complementary to in vitro experiments when studying the physiopathology of dental pulp, new diagnostic tools, or innovative therapeutic strategies. This animal approach makes it possible to define a benefit-risk ratio necessary to be subsequently tested in humans. Among the animal kingdom, rodents, rabbits, ferrets, swine, dogs, and non-human primates have been used to model human pulpitis. The diversity of animals found in studies indicate the difficulty of choosing the correct and most efficient model. Each animal model has its own characteristics that may be advantageous or limiting, according to the studied parameters. These elements have to be considered in preclinical studies. This article aims to provide a thorough understanding of the different animal models used to study pulp inflammation. This may help to find the most pertinent or appropriate animal model depending on the hypothesis investigated and the expected results.